2012
DOI: 10.1002/bdra.22883
|View full text |Cite
|
Sign up to set email alerts
|

Working towards a risk prediction model for neural tube defects

Abstract: BACKGROUND-Several risk factors have been consistently associated with neural tube defects (NTDs). However, the predictive ability of these risk factors in combination has not been evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Each participating mother completed a computer‐assisted telephone interview on exposures before and during pregnancy, including 10 known/highly suspected NTD risk factors: pre‐pregnancy obesity (body mass index ≥30.0), pre‐pregnancy (type I or II) diabetes, gestational diabetes, lack of any folic acid supplementation (folic acid, multivitamin, or prenatal supplement) during the month before pregnancy and the first month of pregnancy (B1–P1), low dietary folate intake (Agopian et al, 2012), anticonvulsant medication use during B1–P1, and any hot tub or sauna use during B1–P1. We also included established nonmodifiable risk factors (female infant sex, family history of NTDs in a first or second‐degree relative, and maternal Hispanic ethnicity) to fully estimate the proportion of NTD cases attributable to all established risk factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each participating mother completed a computer‐assisted telephone interview on exposures before and during pregnancy, including 10 known/highly suspected NTD risk factors: pre‐pregnancy obesity (body mass index ≥30.0), pre‐pregnancy (type I or II) diabetes, gestational diabetes, lack of any folic acid supplementation (folic acid, multivitamin, or prenatal supplement) during the month before pregnancy and the first month of pregnancy (B1–P1), low dietary folate intake (Agopian et al, 2012), anticonvulsant medication use during B1–P1, and any hot tub or sauna use during B1–P1. We also included established nonmodifiable risk factors (female infant sex, family history of NTDs in a first or second‐degree relative, and maternal Hispanic ethnicity) to fully estimate the proportion of NTD cases attributable to all established risk factors.…”
Section: Methodsmentioning
confidence: 99%
“…There are several factors that are known or highly suspected to increase the risk for neural tube defects (NTDs), including female infant sex and family history of NTDs, as well as maternal Hispanic ethnicity, obesity, folate status, pregestational diabetes, gestational diabetes, anticonvulsant use, and hot tub or sauna use (reviewed in Mitchell, 2005). Our previous work demonstrated that these factors poorly predict NTD risk at the population level (Agopian et al, 2012). However, the extent to which these factors account for the population burden of NTDs is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Factors known to increase the risk of NTDs in subsequent pregnancies include birth of a previous child with a NTD, a family history of NTDs, maternal obesity and maternal Hispanic origin, and the use of some anticonvulsants. (48,49) Pregestational or gestational diabetes is of low predictive value,(48) perhaps because the risk may vary with the level of glycemic control. (50) Since the etiology appears to be multifactorial, each risk factor is of similarly low predictive value, with the highest risk being for women with a previous affected child (at 2% to 5% before fortification [24]).…”
Section: Folic Acid Fortification Of Foodsmentioning
confidence: 99%
“…Yet surveillance of brain malformations has only followed trends in anencephaly, microcephaly, and hydrocephalus (Correa et al, ) – all abnormalities that can be diagnosed at birth with 1960's technology. Although surveillance of neural tube defects (NTDs), including anencephaly, has played an important role in the reduction of folic acid responsive NTDs (Agopian et al, ), the overall impact of public health surveillance of congenital brain malformations has been quite modest. Simply stated, surveillance of the frequency of major types of congenital brain malformations based upon modern classifications of brain malformations and routine diagnostic technology is nonexistent in the United States and around the world.…”
Section: Current State Of Congenital Brain Malformation Surveillancementioning
confidence: 99%